2018
DOI: 10.1002/celc.201800302
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Synthesis of NiCo2S4/Graphene Composite for Asymmetric Supercapacitors with Superior Performances

Abstract: To meet the demand of high‐performance electrode materials for supercapacitors, it is highly desirable to design and develop a new class of electrode materials with superior electrochemical performance. Here, we used a simple hydrothermal method to synthesize NiCo2S4‐anchored graphene nanosheets (NiCo2S4/GNS) for high‐performance supercapacitors. Benefiting from the synergistic effect of graphene and NiCo2S4, the as‐prepared composite exhibits outstanding electrochemical performances, such as high specific cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 69 publications
2
16
0
Order By: Relevance
“…2, it can be concluded that Ni 2+ , Co 2+ , Ni 3+ , Co 3+ and S 2− are present in the NiCo 2 S 4 thin films. The XPS results closely agree with previously reported data for NiCo 2 S 4 thin films 30,34 .
Figure 2( a ) Survey spectrum of the optimized NiCo 2 S 4 sample, ( b , c ) Core level spectra for Ni 2p, Co 2p, and S 2p, respectively, at optimized sample NCS:25 thin film on Ni mesh.
…”
Section: Resultssupporting
confidence: 89%
“…2, it can be concluded that Ni 2+ , Co 2+ , Ni 3+ , Co 3+ and S 2− are present in the NiCo 2 S 4 thin films. The XPS results closely agree with previously reported data for NiCo 2 S 4 thin films 30,34 .
Figure 2( a ) Survey spectrum of the optimized NiCo 2 S 4 sample, ( b , c ) Core level spectra for Ni 2p, Co 2p, and S 2p, respectively, at optimized sample NCS:25 thin film on Ni mesh.
…”
Section: Resultssupporting
confidence: 89%
“…Few layers structure of graphene formed by the two reduction methods are evident in their atomic force microscopy images and the corresponding line profiles, Figures 1a and 1b, indicating that each flake approximately contains 3-4 graphene layers.The Raman spectra demonstrate a higher I D /I G ratio (intensity of defect band/intensity of graphitic band) for the FLG formed by borohydride reduction method compared to the corresponding FLG obtained by Fe powder reduction method, ( Figure S1), suggesting the presence of more hydrophilic functionalities in the former. [37,38] This is further clear from the Xray photoelectron spectra (XPS), Figure 1c, where carbon attached to oxygen functionalities are evidently present in FLG obtained by borohydride reduction method. Such signals are negligible in the case of FLG obtained by Fe powder reduction method.…”
mentioning
confidence: 71%
“…To further evaluate NiCo 2 O 4 /MnO 2 core/shell composites electrode for real application, a series of asymmetric supercapacitor devices are assembled by using NiCo 2 O 4 /MnO 2 core/shell composites electrode as the cathode and biochar as the anode in 6 M KOH electrolyte with one piece of PTFE film as the separator . Three types of biochar (pomelo peel (PPC), banana peel (BPC) and buckwheat hull (BHC)) are processed (schematic ).…”
Section: Introductionmentioning
confidence: 90%